VD_FINDINFO Réc-civile / 2014 / 29 vom 12. August 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, AUTORITÉ DE RECOURS, COMPORTEMENT, TÉMOIN, DÉBAT DU TRIBUNAL | 106 al. 1 CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ